THE EVOLUTION OF EUROPEAN BUSINESS ENVIRONMENT IN THE LAST FOUR YEARS - Danu, Cornelia Marcela (Studies and Scientific Researches. Economics Edition, 2015)
In the present work I described the evolution of the main coordinates of the business environment in the countries of Europe. I examined the dynamics of economic growth, inflation, budget balance, current account balance, public debt for 41 European countries, taking into account their delimitation of regional groups. Analysis of the business environment in the countries of Europe using the indicators "assessment of the business climate" and "country risk" is aimed at identifying signals which are transmitted by the national economies, to the system of European economy, to the system of global economy but, in particular, the application optimal policies for improving the quality of the societal environment on the continent. I analyzed the impact of economic growth and inflation on business development, establishing relations between the rate of economic growth - the dynamics of the number of enterprises, the rate of inflation - the dynamics of the number of enterprises from 19 countries in Europe.